Interleukin-10 in the Pathophysiology of Inflammatory Bowel Disease: Increased Serum Concentrations During the Recovery Phase - Keiichi Mitsuyama; Nobuo Tomiyasu; Kosuke Takaki; Junya Masuda; Hiroshi Yamasaki; Kotaro Kuwaki; Teiko Takeda; Shigehiko Kitazaki; Osamu Tsuruta; Michio Sata (Mediators of Inflammation)
Using a specific enzyme-linked immunosorbent assay, IL-10 concentrations were measured in serum from 62 patients with ulcerative colitis (UC), 43 with Crohn's disease (CD), 25 with other colitides, and 44 normal control subjects. Serum IL-10 concentrations were increased in patients with active UC but not in those with active CD when compared with normal control subjects. A time course study showed that in patients with UC and CD, serum concentrations of IL-6 and C-reactive protein increased during the acute phase and returned to normal as patients go into remission. Notably, serum IL-10 concentrations increased during the phase of disease resolution and declined thereafter regardless of the treatment modality. Gel filtration analysis indicated that IL-10 circulated predominantly as a dimer. In conclusion, this study shows that serum IL-10 is increased during disease recovery in patients with inflammatory bowel disease, and may be a helpful marker in monitoring disease status.